Recent Advances in Sequentially Pd-Catalyzed One-Pot Syntheses of Heterocycles - Maryna M. Kornet; Thomas J. J. Müller (Molecules)
Sequential Pd-catalyzed one-pot synthetic methodologies have emerged as a powerful and versatile approach in organic synthesis, enabling the construction of complex heterocyclic architectures with high efficiency, selectivity, and atom economy. This review discusses key advancements in multistep, sequentially Pd-catalyzed one-pot processes for accessing heterocyclic derivatives, focusing on classic reactions like Suzuki–Miyaura, Sonogashira, Heck, and hydroamination and extending to specialized techniques such as directed C-H activation. The concatenation of these steps has advanced the scope of one-pot strategies. A section is dedicated to exploring the cooperative use of palladium with other metals, particularly copper, ruthenium, and gold, which has broadened the range of accessible heterocyclic derivatives. Highlighted applications include the synthesis of biologically and pharmaceutically relevant compounds, such as tris(hetero)aryl systems, spiro-oxindoles, and indole derivatives. These one-pot strategies not only streamline synthesis but also align with green chemistry principles by minimizing purification steps and reducing waste and energy consumption. The review also addresses current challenges and limitations in these methodologies, offering insights into ongoing efforts to optimize reaction conditions and expand the applicability of sequential Pd-catalyzed processes.